2011
DOI: 10.1155/2011/382473
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection byAspergillusand Zygomycetes Species in a Case of Acute Rhinosinusitis

Abstract: Invasive mycotic infections can be effectively treated if rapid identification of fungus is obtained. We reported a case of coinfection by Aspergillus and Rhizopus sp. involving nose, paranasal sinuses, orbit, and brain in a 68-year-old known hypertensive male. He was presented to ENT OPD with history of fever and intermittent headache since fifteen days along with history of right-sided nasal obstruction and proptosis since seven days. CT scan of brain and paranasal sinuses showed findings of pansinusitis wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…that are more commonly seen in diabetic patients, particularly in the setting of DKA as was seen in this patient [1] . Invasive fungal infections of the oro-rhinocerebral area, due to mixed mucormycosis and aspergillosis infections have rarely been reported [2] , [3] , [4] , [5] , [6] .…”
Section: Case Reportmentioning
confidence: 99%
“…that are more commonly seen in diabetic patients, particularly in the setting of DKA as was seen in this patient [1] . Invasive fungal infections of the oro-rhinocerebral area, due to mixed mucormycosis and aspergillosis infections have rarely been reported [2] , [3] , [4] , [5] , [6] .…”
Section: Case Reportmentioning
confidence: 99%
“…6 Vaidya D also reported a case of 68 years male with headache and proptosis and was diagnosed as having sinonasal mucormycosis and aspergillosis and was managed by surgical debridement and antifungals. 7 Maiorano E et al also reported a case of combined infection with mucormycosis and aspergillosis in a patient with Casleman's disease. 8 Zygomycosis is a serious opportunistic infections that is commonly seen in immunocompromised patients.…”
Section: Discussionmentioning
confidence: 97%
“…Unfortunately, that patient did not respond well to treatment and succumbed to his illness, probably due to a delay in diagnosis and treatment [ 14 ]. Another case was reported from India in Gujarat in 2011, where co-infection of Aspergillus species and Rhizopus species in rhinocerebral sinusitis was contained by antifungal treatment and the patient made a full recovery [ 9 ]. In the current case, prompt diagnosis and treatment also controlled the fatal fungal co-infection, leading to complete recovery of the patient with no sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…Co-infection of aspergillosis and mucormycosis in sinuses is apparently a rare entity that is difficult to diagnose, posing clinical dilemmas, and very few such cases have been reported with recovery in the literature [ 9 ]. Here, we report an unusual case of rhinocerebral zygomycosis with aspergillosis in a 60-year-old diabetic patient, who recovered completely from this fatal co-infection due to timely diagnosis and treatment .…”
Section: Introductionmentioning
confidence: 99%